Rhoda‐Electrocatalyzed Bimetallic C−H Oxygenation by Weak O‐Coordination. Issue 24 (7th May 2021) - Tan, Xuefeng; Massignan, Leonardo; Hou, Xiaoyan; Frey, Johanna; Oliveira, João C. A.; Hussain, Masoom Nasiha; Ackermann, Lutz
Abstract: Rhodium‐electrocatalyzed arene C−H oxygenation by weakly O ‐coordinating amides and ketones have been established by bimetallic electrocatalysis. Likewise, diverse dihydrooxazinones were selectively accessed by the judicious choice of current, enabling twofold C−H functionalization. Detailed mechanistic studies by experiment, mass spectroscopy and cyclovoltammetric analysis provided support for an unprecedented electrooxidation‐induced C−H activation by a bimetallic rhodium catalysis manifold. Abstract : Rhodium‐electrocatalyzed C−H oxygenations of amides and ketones proved viable under mild conditions via bimetallic electrocatalysis. Mechanistic studies revealed a high‐valent dimeric rhodium electrocatalysis.